Who was who in Jachymov mineralogy II - Veselovsky,F.; Ondrus,P.; Gabasova,A.; Hlousek,J.; Vlasimsky,P.; Chernyshev,I.V. (Journal of the Czech Geological Society, 2003)
The paper presents biographic data of persons, after whom new primary minerals discovered at Jachymov were named (K. Sternberg, W. H. Miller, G. A. Krutov), as well as the recently discovered secondary minerals (J. Vajdak, J. Cejka, J. Svenek). Biographics of scientists who described new minerals from Jachymov are given in the following part (F. E. Bruckmann, I. Born, A. G. Werner, H. Dauber, G. A. Kenngott, W. Sartorius v. Waltershausen, F. Sandberger, R. Novacek, R. A. Vinogradova). Biographies of persons who significantly contributed to mineralogy of the Jachymov ore district are presented in the last section (F. Babanek, J. Step, R. Zuckert, R. P. Dubinkina, R. V. Geceva, F. Mrna, M. Komarek, D. Pavlu). This contribution is a continuation of the 1997 article Who was who? - In names of secondary minerals discovered in Jachymov [561] dealing exclusively with secondary minerals.
Keywords: Jachymov; biographies of scientists; mineralogists; names of mineral species